Development and characterization of an inducible Dicer conditional knockout mouse model of Parkinson’s disease: validation of the antiparkinsonian effects of a sigma-1 receptor agonist and dihydromyricetin - Guo Chen-hong; Cao Ting; Zheng Long-tai; Waddington John L; Zhen Xue-chu (Acta Pharmacologica Sinica; Vol 41, No 4 (April 2020): Acta Pharmacologica Sinica (Special Feature on Drug Research and Diagnosis of Parkinson’s Disease), 2020)
Parkinson’s disease (PD) is a common neurodegenerative disease characterized by motor impairment and progressive loss of dopamine (DA) neurons. At present, the acute application of neurotoxic drugs such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 6-hydroxydopamine (6-OHDA) are commonly used to simulate the pathology of PD; however, it is difﬁcult to induce the progressive pathogenesis of PD with these models. In this study, we employed DAT promoter-mediated Cre transgenic mice to establish tamoxifen-inducible Dicer conditional knockout (cKO) mice in an effort to mimic the progressive loss of DA neurons and the development of PD-like behavioral phenotypes. The results showed that Dicer cKO mice exhibited progressive loss of DA neurons in the substantia nigra (SN) following tamoxifen administration. Signiﬁcant DA loss was observed 6 weeks after tamoxifen administration; accordingly, progressive motor function impairment was also observed. We also found that a signiﬁcant neuroinﬂammatory response, as evidenced by microglial proliferation, another hallmark of PD pathogenesis, accompanied the loss of DA neurons. The acute application of levo-DOPA (L-DOPA) relieved the PD-like motor impairments in Dicer cKO mice to exert its antiparkinsonian action, indicating that the model can be used to evaluate the antiparkinsonian efﬁcacy of PD drugs. To further elucidate the potential application of this novel PD animal model for PD drug development, we employed the powerful neuroprotective agent dihydromyricetin (DHM) (10 mg/kg) and the selective sigma-1 receptor agonist PRE-084 (1 mg/kg), both of which were previously shown to produce antiparkinsonian effects. The results indicated that the chronic administration of either DHM or PRE-084 attenuated the Dicer cKO-induced loss of DA neurons and motor impairments, although the two drugs acted through different mechanisms. These data indicate that the Dicer cKO mouse model may be a useful model for investigating the pathological development of PD and intervention-mediated changes. In conclusion, this transgenic mouse model appears to simulate the progressive pathogenesis of PD and may be a potentially useful model for PD drug discovery.